Environmental impacts and risk assessment in the re-use of Cr-bearing pyrolyzed tannery wastes: A case study in a residential area - Lisa Ghezzi; Simone Arrighi; Enrico Mugnaioli; Natale Perchiazzi; Erika Zamponi; Simone Pollastri; Fabrizio Franceschini; Riccardo Petrini (Applied Geochemistry, 2024)

What, where, and when: Spatial-temporal distribution of macro-litter on the seafloor of the western and central Mediterranean sea - Alessandro Cau; Alice Sbrana; Simone Franceschini; Fabio Fiorentino; Maria Cristina Follesa; Francois Galgani; Germana Garofalo; Olivia Gerigny; Adriana Profeta; Paola Rinelli; Mario Sbrana; Tommaso Russo (Environmental Pollution, 2024)

Meso- and microplastic composition, distribution patterns and drivers: A snapshot of plastic pollution on Brazilian beaches - Tamyris Pegado; Ryan Andrades; Eurico Noleto-Filho; Simone Franceschini; Marcelo Soares; David Chelazzi; Tommaso Russo; Tania Martellini; Angelica Barone; Alessandra Cincinelli; Tommaso Giarrizzo (Science of The Total Environment, 2024)

A deep learning model for measuring coral reef halos globally from multispectral satellite imagery - Simone Franceschini; Amelia C. Meier; Aviv Suan; Kaci Stokes; Samapriya Roy; Elizabeth M.P. Madin (Remote Sensing of Environment, 2023)

Experimental investigation on anti-falling protection systems for reinforced concrete-brick composite floors - Lorenzo Franceschini; Beatrice Belletti; Daniele Ferretti; Alice Sirico; Simone Ravasini; Federico Pagliari; Andrea Vitali; Paolo De Berardinis (Engineering Structures, 2023)

From inshore to offshore: distribution of microplastics in three Italian seawaters - Alice Sbrana; Tommaso Valente; Jessica Bianchi; Simone Franceschini; Raffaella Piermarini; Flavia Saccomandi; Andrea Giuseppe de Lucia; Andrea Camedda; Marco Matiddi; Cecilia Silvestri (Environmental Science and Pollution Research, 2022)
A comprehensive understanding of the concentration of microplastics (MPs) in seawaters is essential to implement monitoring programs and understand the impacts on ecosystems, as required by the European legislation to protect the marine environment. In this context, the purpose of this study is to investigate the composition, quantity, and spatial distribution of microplastics from coastal to offshore areas in three Italian seawaters. In addition, the distribution of microplastics between surface and subsurface water layers was analyzed in order to better understand the dynamics of MPs in the upper layers of the water column. A total number of 6069 MPs (mean total concentration of 0.029 microplastics · m −2 ) were found to be heterogeneous in type, shape, and color. In general, MPs concentrations decrease with coastal distance, except when environmental forcings are predominant (such as sea currents). Moreover, the amount of surface MPs was almost four times that of subsurface microplastics, which consisted mostly of fibers. In light of these results, it becomes clear how critical it is to plan remediation actions and programs to minimize microplastic accumulations in the sea.

Ask the shark: blackmouth catshark (Galeus melastomus) as a sentinel of plastic waste on the seabed - Alice Sbrana; Alessandro Cau; Davide Cicala; Simone Franceschini; Tommaso Giarrizzo; Maria Flavia Gravina; Alessandro Ligas; Giulia Maiello; Marco Matiddi; Antonio Parisi; Paolo Sartor; Mario Sbrana; et al. (Marine Biology, 2022)
The presence of plastic waste in the marine environment has driven the scientific community to make significant efforts to study and mitigate its possible effects. One of the critical aspects is to determine if and how an increase in ingestion events may occur as a result of the accumulation of plastic waste on the seabed. In this study, G. melastomus is examined for its ability to indirectly provide information on the amount of macroplastics accumulating on the seafloor. Plastic ingestion is explored by describing the feeding habits of the species, which have the potential to provide very useful information regarding biological or ecological issues. The diet of G. melastomus mainly consisted of cephalopods, bathypelagic fishes, and decapod crustaceans, increasing in diversity during growth. The generalist-opportunistic feeding behaviour of this species leads to the incidental ingestion of plastic particles ( N = 47, with a mean (± SD) of 1.47 ± 0.28 per specimen) which can be indirectly associated to the presence of macroplastics on the seafloor. Indeed, our results indicate a significant relationship between the amount of macroplastics present on the seabed and the frequency of ingestion of plastic particles by blackmouth catshark. We propose G. melastomus as an excellent candidate for developing a valid monitoring strategy for the presence of plastics on the seabed, as requested by the EU Marine Strategy Framework Directive.

Defend as You Can, React Quickly: The Effects of the COVID-19 Shock on a Large Fishery of the Mediterranean Sea - Tommaso Russo; Elena Catucci; Simone Franceschini; Lucio Labanchi; Simone Libralato; Evelina Carmen Sabatella; Rosaria Felicita Sabatella; Antonio Parisi; Fabio Fiorentino (Frontiers in Marine Science, 2022)
This paper presents an analysis of the effect of SARS-CoV-2 coronavirus pandemic and related restrictive measures on the activity of the Italian fleet of trawlers, which represents one of the most important fisheries in the Mediterranean Sea. We integrated multiple sources of information including: (1) Fleet activity data from Vessel Monitoring System, the most important satellite-based tracking device; (2) vessel-specific landing data disaggregated by species; (3) market and economic drivers affecting the effort variation during the lockdown and in the related fishing strategies; (4) monthly landings of demersal species in the main Italian harbors. These data sources are combined to: (1) Assess the absolute and relative changes of trawling effort in the geographical sub-areas surrounding the Italian coasts; (2) integrate and compare these changes with the market and economic drivers in order to explain the observed changes in fishing effort and strategy; (3) analyze the changes of the fishing effort on the Landing-per-unit-effort (LPUE) in order to further understand the strategy adopted by fishers during this crisis and to infer the potential consequence for the different stocks. The results provide an overview of the effects of the “COVID-19 shock,” in terms of fishing activity and socio-economic drivers, demonstrating that the consequences of the pandemic have been very varied. Although the COVID-19 shock has caused a marked overall reduction in activity in the first semester of 2020, in some cases the strategies adopted by fishermen and the commercial network linked to their activity have significantly reduced the impact of the emergency and taken back catch and effort to levels similar to those of previous years. These results could provide insights for management measures based on temporal stops of fishing activities. In particular, if no limits to the fishing effort after the restart of fishing activities are adopted, the benefits of fishing pressure reduction on fishery resources could be nullified. On the other hands, when fishing activities restart, and in the absence of catch control, effort tends to increase on coastal bottoms characterized by greater abundance of resources and longer effective fishing time.

Early germline differentiation in bivalves: TDRD7 as a candidate investigational unit for Ruditapes philippinarum germ granule assembly - Beatrice Filanti; Giovanni Piccinini; Simone Bettini; Maurizio Lazzari; Valeria Franceschini; Maria Gabriella Maurizii; Liliana Milani (Histochemistry and Cell Biology, 2021)
The germline is a key feature of sexual animals and the ways in which it separates from the soma differ widely across Metazoa. However, at least at some point during germline differentiation, some cytoplasmic supramolecular structures (collectively called germ plasm-related structures) are present and involved in its specification and/or differentiation. The factors involved in the assembly of these granular structures are various and non-ubiquitous among animals, even if some functional patterns and the presence of certain domains appear to be shared among some. For instance, the LOTUS domain is shared by Oskar, the Holometabola germ plasm master regulator, and some Tudor-family proteins assessed as being involved in the proper assembly of germ granules of different animals. Here, we looked for the presence of LOTUS-containing proteins in the transcriptome of Ruditapes philippinarum (Bivalvia). Such species is of particular interest because it displays annual renewal of gonads, sided by the renewal of germline differentiation pathways. Moreover, previous works have identified in its early germ cells cytoplasmic granules containing germline determinants. We selected the orthologue of TDRD7 as a candidate involved in the early steps of germline differentiation through bioinformatic predictions and immunohistological patterning (immunohistochemistry and immunofluorescence). We observed the expression of the protein in putative precursors of germline cells, upstream to the germline marker Vasa. This, added to the fact that orthologues of this protein are involved in the assembly of germ granules in mouse, zebrafish, and fly, makes it a worthy study unit for investigations on the formation of such structures in bivalves.

Eating Near the Dump: Identification of Nearby Plastic Hotspot as a Proxy for Potential Microplastic Contamination in the Norwegian Lobster (Nephrops norvegicus) - Simone Franceschini; Alessandro Cau; Lorenzo D’Andrea; Maria Cristina Follesa; Tommaso Russo (Frontiers in Marine Science, 2021)
Plastic waste dumped in the marine environment has severe ecological, social and economic impacts. In recent years, a series of scientific studies documented the contamination by macroplastic and its impact on marine organisms through the accidental ingestion of microplastics, which also originate from the degradation of macroplastic. However, the relationship between the spatial distribution of marine litter and the ingestion of plastics by organisms have never been related. In this work, we aimed to investigate, through a modeling approach, the relations between potential sources of microplastic particles (i.e., seafloor macroplastic accumulation hotspots detected by means of trawl surveys), and the ingestion by the benthic crustacean Norwegian lobster ( Nephrops norvegicus ). According to the literature, N. norvegicus is characterized by a sedentary behavior and therefore it has been highlighted as a proficient sentinel species for local microplastic contamination. Despite no significant relation has been found between microplastic ingestion and the local presence of seafloor macroplastic, it seems that proximity to hotspots of macroplastic accumulation is significantly related to microplastics ingestion. These results highlight important considerations on the fate of plastic in the marine environments with significant impacts on biota and the quality of the product caught at sea.

The MINOUWApp: a web-based tool in support of by-catch and discards management - Lorenzo D’Andrea; Aida Campos; Karim Erzini; Paulo Fonseca; Simone Franceschini; Stefanos Kavadas; Irida Maina; Francesc Maynou; Tommaso Russo (Environmental Monitoring and Assessment, 2020)
Current fishing practices often do not allow adequate selection of species or sizes of fish, resulting in unwanted catches, subsequently discarded, with the consequent negative effects on both marine communities and fisheries profitability. The cross-analysis of density patches of potential unwanted catches and distribution of fishing effort can support the identification of spatial-temporal hot-spots in which the fishing pressure should be reduced to limit the amount of discards. The MinouwApp represents a technological and methodological framework to bring different, and structurally complex, sources of georeferenced data together into a simple visual interface aiming to interactively explore temporal ranges and areas of interest. The objective is to improve the understanding of fisheries dynamics, including discards, thus contributing to the implementation of discard management plans in a context of participative, ecosystem-based fisheries management strategies.

Consumer Preferences for Farmed Seafood: An Italian Case Study - Domitilla Pulcini; Simone Franceschini; Luca Buttazzoni; Cristina Giannetti; Fabrizio Capoccioni (Journal of Aquatic Food Product Technology, 2020)

Predicting Fishing Footprint of Trawlers From Environmental and Fleet Data: An Application of Artificial Neural Networks - Tommaso Russo; Simone Franceschini; Lorenzo D’Andrea; Michele Scardi; Antonio Parisi; Stefano Cataudella (Frontiers in Marine Science, 2019)

Simulating the Effects of Alternative Management Measures of Trawl Fisheries in the Central Mediterranean Sea: Application of a Multi-Species Bio-economic Modeling Approach - Tommaso Russo; Lorenzo D'Andrea; Simone Franceschini; Paolo Accadia; Andrea Cucco; Germana Garofalo; Michele Gristina; Antonio Parisi; Giovanni Quattrocchi; Rosaria Felicita Sabatella; Matteo Sinerchia; Donata M. Canu; et al. (Frontiers in Marine Science, 2019)

Trends in Effort and Yield of Trawl Fisheries: A Case Study From the Mediterranean Sea - Tommaso Russo; Paolo Carpentieri; Lorenzo D’Andrea; Paola De Angelis; Fabio Fiorentino; Simone Franceschini; Germana Garofalo; Lucio Labanchi; Antonio Parisi; Michele Scardi; Stefano Cataudella (Frontiers in Marine Science, 2019)

Crypt cell markers in the olfactory organ of Poecilia reticulata: analysis and comparison with the fish model Danio rerio - Simone Bettini; Liliana Milani; Maurizio Lazzari; Maria Gabriella Maurizii; Valeria Franceschini (Brain Structure and Function, 2017)

VASA expression suggests shared germ line dynamics in bivalve molluscs - Liliana Milani; Andrea Pecci; Fabrizio Ghiselli; Marco Passamonti; Simone Bettini; Valeria Franceschini; Maria Gabriella Maurizii (Histochemistry and Cell Biology, 2017)

Immunocytochemical characterisation of ensheathing glia in the olfactory and vomeronasal systems of Ambystoma mexicanum (Caudata: Ambystomatidae) - Maurizio Lazzari; Simone Bettini; Valeria Franceschini (Brain Structure and Function, 2016)

Immunocytochemical characterization of olfactory ensheathing cells in fish - Maurizio Lazzari; Simone Bettini; Valeria Franceschini (Brain Structure and Function, 2013)